Full-endoscopic Spine Surgery for the Treatment of Lumbar Ligamentous Flavum Hematoma - Chia-Wei CHANG; Ryoji TOMINAGA; Yasushi OSHIMA; Hiroki IWAI; Hirohiko INANAMI; Hisashi KOGA (Neurologia Medico-Chirurgica)
Lumbar ligamentous flavum hematoma (LFH) is a relatively rare pathology, and it is difficult to differentiate it from other cystic lesions. Full-endoscopic spine surgery (FESS), an excellent approach for clear and magnified operative visual field since it allows saline irrigation and minimizes destruction of surrounding tissues, has been applied to the treatment. This study aims to present a case series of patients with lumbar LFH treated by FESS. This case series consists of 17 lumbar LFH cases treated by FESS between May 2018 and November 2021 at a single institution. Patient background and operative data were collected from their medical records. The numerical rating scale (NRS), Oswestry Disability Index (ODI), and European Quality of Life-5 Dimensions (EQ-5D) were recorded preoperatively and postoperatively. Elderly men tend to suffer from lumbar LFH at the L4/5 vertebral level. Discontinuity with facet joint was confirmed under endoscopic visualization in all 17 cases. Blood clots were also observed in all cases under endoscope. The mean operative time was 68.6 min without complication. The patients were discharged at average 1.4 days after FESS with significant improvement of NRS score (P < 0.001). ODI and EQ-5D scores 2-year postoperatively statistically improved (P < 0.001), and there was no recurrence during followup period. The operative outcomes of lumbar LFH treated by FESS were satisfactory. FESS excels not only in the diagnosis but also in the treatment of lumbar LFH.